Finogel - halal nanomaterials from fish collagen extracts - Jaswir, Irwandi; A. Monsur, Hammed Ademola; Mohd. Salleh, Hamzah (2010)
Finogel is a gelatin extract from fish (perch) skin. It is 100% protein, nano coil-tubular structures, pure white coloration, high solubility and other functional properties. When reconstituted, it behaves like Newtonian fluid. It is categorized as Type A and B due to its molecular composition. It is in the form of dried powder. Generally, gelatin, one of the most popular biopolymers, is widely used in food (confectionary, dairy products, bakery, low fat spreads, meat product beverages), pharmaceutical (hard capsule, soft capsules, coatings, plasma expanders), wound care (surgical/dental sponges, hydrocolloids dressings) cosmetic , and photographic(silver halide crystal-containing emulsion layer, coating layer, sub-coating layer, antihalogen layers and non-curl layer) applications because of its unique functional and rheological properties. It can act as binder, bioactive carrier for drug delivery, amino acids supplements, encapsulating agent, wound healing, clarification, texturizer, etc. Finogel is an improved product. It is quite distinct from all available fish gelatin due to the intrinsic qualities which make it a direct match with mammalian gelatin. In order to achieve improvement in production of Finogel, the production process was studied, modified and optimized. This lead to the eradication in associated negative qualities of fish gelatin like fishy odour, low gel-strength, low melting point, turbidity and low yield. In fact, Finogel is quite very high in gel-strength. Gel-strength is a very important parameter of gelatin, measured in bloom and determine its market value. High bloom value commands high price and vice versa.